Performance of GIS interfaces in Watershed Delineation and Stream Network Generation from DEM - Sarangi, A; Madramootoo, C A; Singh, D K; Singh, A K (Journal of Agricultural Engineering, 2004)
The Geographic Information System (GIS) tool is efficient in delineating drainage area and generating surface drainage network. Watershed delineation and natural drainage network generation from Digital Elevation Models (DEMs) are the preliminary steps for watershed prioritization, integrated watershed management (IWM) and sustainable development of natural resources within the watershed. In the present study, recently developed GIS supported interfaces within ArcGIS 8.x and ArcVfew 3.0 software were applied to accomplish these tasks. The DEM of Cowansvile region, Quebec, Canada was used in the present study for delineation of watersheds. The interfaces performed a sequence of activities such as filling the sinks, estimating the flow direction, flow accumulation and stream links to arrive at delineation of watershed from DEMs and generation of drainage networks. In the present study, the interfaces viz. Watershed and Stream Delineation Tool (WSDT), Terrain analysis using DEMs (TauDEM), Watershed Morphology Estimation Tool (WMET) used within ArcGIS 8.x environment and Centre for Research in Water Resources Pre-Processor (CRWR Pre-Pro) interfaces within ArcView 3.x environment were used. It was reveled that the interfaces within the ArcGIS 8.x performed better than that with the Arc View 3.x environment in terms of processing time and accuracy.